Pengembangan Materi Hadits tentang Tanggung Jawab Kepemimpinan Berbasis Living Hadith melalui Living Hadith Project pada Siswa Kelas XI MA Pondok Pesantren Darul Hikamah Darussalam Kapuas - Ahmad Ahmad; Jamaludin Jamaludin; Mardhiya Agustina (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2026)
This study was motivated by students' limited understanding and application of the hadith values concerning leadership responsibility in their daily lives. This condition highlights the need for an innovative learning approach that not only emphasizes conceptual understanding but also encourages the internalization of hadith values through authentic learning experiences. The study aims to develop hadith learning materials based on the living hadith approach through a living hadith project using the ADDIE instructional design model. This research employed a Research and Development (R&D) method consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The participants were eleventh-grade students of MA Pondok Pesantren Darul Hikamah Darussalam Kapuas, an Islamic boarding school implementing a residential education system. Data were collected through classroom observations, cognitive tests, students' reflective journals, and documentation. The findings indicate that the living hadith project effectively enhances students' understanding of leadership responsibility as taught in the hadith and encourages them to practice responsibility, discipline, and social awareness in both the school and boarding school environments. Consequently, this learning model creates a more contextual, participatory, meaningful, and experience-based learning process that is relevant to students' everyday lives.